ChemInform Abstract: Diastereoselective Intermolecular Ene Reactions: Synthesis of 4, 5, 6, 7‐Tetrahydro‐1H‐benzo[d]imidazoles. Issue 6 (20th February 2013) - Watson, Lynsey J.; Harrington, Ross W.; Clegg, William; Hall, Michael J.
Abstract Starting materials (I) and (X) are prepared by Diels—Alder reaction of the corresponding vinyl‐imidazole precursors.